Simulation-Based Teaching in Increasing Knowledge of Expressed Breast Milk Management in Baby Mothers - Nirmala K.S; Elfi Quyumi Rahmawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2024)
Exclusive breastfeeding had many benefits for mothers and babies. Maternal employment was one of the factors that was closely related to the decline in exclusive breastfeeding coverage. Therefore, there was a need for education for mothers of toddlers to continue providing breast milk even though they are working. Objective of this research was to analyze the effect of simulation-based teaching on about the management of expressed breast milk on the mother's knowledge of the baby in Toddler Posyandu in Pelem Village, Bendo Community Health Center. The method was research quantitative. The reasearch was carried out at the Posyandu Balita in Pelem Village, Bendo Community Health Center on Saturday, January, 20th 2024. This activity was attended by 40 mothers of toddlers. There was an influence of health education using the simulation-based teaching method on the mother's knowledge about the management of expressed breast milk with a wilcoxon test result of 0.002.